Crystallization of the membrane-containing bacteriophage PRD1 in quartz capillaries by vapour diffusion. - Cockburn, J; Bamford, J; Grimes, J; Bamford, D; Stuart, D (2003)
Crystals of bacteriophage PRD1, a virus containing an internal lipid bilayer, have been grown in thin-walled quartz capillary tubes by vapour diffusion as a means of eliminating mechanical handling of the crystals during data collection. It has been found that the addition of polyethylene glycol 20 000 (PEG 20K) to the mother liquor that bathes the crystals allows far higher resolution diffraction intensities to be observed. Growing and treating the crystals in this way has produced a small number of crystals which are particularly amenable to X-ray diffraction analysis.